The influence of the pseudoexfoliation syndrome on cataract development - Napora, Katarzyna; Obuchowska, Iwona; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Pseudoexfoliation syndrome (PEX) is a chronic, systemic, connective tissue disease. Its hallmark is the accumulation of an abnormal, amyloid-like material in the anterior segment tissues of the eye. PEX is one of the risk factors in the development of lens opacification. The aim of the paper is a presentation of the current knowledge on the relationship between pseudoexfoliation syndrome and cataract. Special attention is paid to pathogenetic and epidemiologic factors